LC–MS/MS multiplexed assay for the quantitation of a therapeutic protein BMS-986089 and the target protein Myostatin. (February 2016) - Zhu, Yongxin; D'Arienzo, Celia; Lou, Zhen; Kozhich, Alexander; Madireddi, Malavi; Chimalakonda, Anjaneya; Tymiak, Adrienne; Olah, Timothy V
Background: Therapeutic protein discovery study highlights the need for the development of quantitative bioanalytical methods for determining the levels of both the therapeutic protein and the target protein, as well.Results: For the quantitation of BMS-986089, both accuracy (99–103%) and precision (2.4–12%) were obtained for the analysis of the surrogate peptide (ITYGGNSPVQEFTVPGR), in addition to the accuracy (100–108%) and precision (0.7–18%) that were obtained for the analysis of the surrogate peptide (VVSVLTVLHQDWLNGK). For Myostatin, accuracy (94–103%) and precision (2.4–14.9%) were obtained for the analysis of the surrogate peptide (IPAMVVDR).Conclusion: The developed method was applied to the analysis of samples following dosing of BMS-986089 to mice. This method highlights the potential of LC–MS/MS-based methods to eventually assess in vivo drug–target engagement.